PEMANFAATAN APLIKASI KASIR DAN SISTEM AKUNTANSI SEDERHANA TERHADAP PENGAMBILAN KEPUTUSAN UMKM MIKRO KECIL - Putri P, Andi Sri Kumala; Haliah, Haliah; Darmawati, Darmawati (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to examine the partial and simultaneous influence of the use of digital cashier applications and simple accounting systems on the quality of decision-making in Micro and Small Enterprises (MSEs) in Sidenreng Rappang Regency. The MSE sector, despite contributing dominantly to the economy, still faces challenges in weak financial recording practices. Field phenomena show that the adoption of cashier applications is often partial and only trend following, not maximized as a simple accounting system. This study uses a quantitative approach with a survey method, involving 30 micro and small MSEs as a sample through purposive sampling techniques. The data was analyzed using Multiple Linear Regression Analysis with SPSS software. The results of the hypothesis test showed that (H1) the use of cashier applications (Sig. 0.003; Koef. 0.421) and (H2) the use of a simple accounting system (Sig. 0.012; Koef. 0.356) partially has a positive and significant effect on the quality of MSE decision-making. Furthermore, (H3) both variables simultaneously had a significant effect on the quality of decision-making (Sig. 0.000) The coefficient of determination of 0.568 shows that 56.8% variation in the quality of decision-making can be explained by this model. The results of the study concluded that the synergy between the digitization of transaction recording and the implementation of a simple accounting system is very important in improving MSE business decisions